Isabella é uma rosa impedida de desabrochar em nosso jardim – Uma análise das expressões metafóricas na conceitualização de violência - Menezes, Léia Cruz de (2012)
“Angel” [six-year-old girl] versus “monsters” [biological father and step-mother] in the center of a “circus” [media broadcasting] that feed a massive vocation to “bend the log” [make justice]. Why the use of metaphor in the conceptualization of violence in the everyday language? In this article, we state that the metaphor is justified for being part of the human system of though organization, though, a mechanism which allows us to be part of the universe (LAKOFF; JOHNSON, 1980). Using the conceptualization of metaphor established by Grady (1997), we analyze how the sharing of features among the conceptual domains projected in the metaphors of constitutive similarity found in the readers’ comments of Ricardo Noblat’s blog along the discussion of the Isabella Nardoni police case takes place and proceed a reading of feelings of empathy and antagonism present in the speech objects construction through the metaphor.